WATER DEFICIENCY ON THE MAIZE GRAIN YIELD DECREASE IN THE CATARINENSE FAR WEST - GUADAGNIN, CLÍSTENES ANTÔNIO; SCHOFFEL, EDGAR RICARDO; CASALINHO, HELVIO DEBLI; BACIC, IVAN LUIZ ZILLI (International Journal of Maize & Sorghum, 2017)
ABSTRACT - Maize is of fundamental social economical importance for familiar agriculture in the west of the State of Santa Catarina. In this region, the decrease of grain yield of the culture is frequently related to periods of water deficiency. The purposes of the present study were to assess the maize grain yield decrease due to water deficiency, identify the sowing time with a lower risk of water deficiency and determine and probability of risks of grain yield decrease. The grain yield decrease was calculated using the Isareg model, based on the ten-day water balance, for the period between1989/90 to 2010/11, simulated for nineteen sowing dates and three cycles of maize maturation. The model estimated an average grain yield decrease of 25.1%. The biggest decrease took place in the initial sowing of August and the smallest in the late sowings between January and February, with a maximum variation of 3.9% between the assessed maturation cycles. The Isareg model is appropriate to estimate the grain yield decrease, however it overestimates its value when the relative evapotranspiration is above 0.8. The levels of 40% of grain yield decrease present 10.5% of probability of occurrence. Keywords: drought, hydric balance, simulation model, sowing time, crop yield losses. DEFICIÊNCIA HÍDRICA NA REDUÇÃO DE PRODUTIVIDADE DO MILHO NO OESTE CATARINENSE RESUMO - O milho é de fundamental importância socioeconômica para a agricultura familiar da região do Extremo Oeste Catarinense. Nessa região, a redução da produtividade da cultura está frequentemente relacionada aos períodos de deficiência hídrica. Os objetivos deste estudo foram avaliar a redução de produtividade de milho devido à deficiência hídrica, identificar as épocas de semeadura com menor risco de deficiência hídrica e determinar a probabilidade de riscos de redução de produtividade. A redução de produtividade foi calculada pelo modelo Isareg, baseado no balanço hídrico decendial, para o período 1989/90 a 2010/11, simuladas para dezenove datas de semeadura e três ciclos de maturação de milho. O modelo estimou uma redução de produtividade média de 25,1%. A maior redução ocorreu na semeadura inicial de agosto e a menor nas semeaduras tardias entre janeiro e fevereiro, com variação máxima de 3,9% entre os ciclos de maturação avaliados. O modelo Isareg é apropriado para estimar a redução de produtividade, entretanto superestima seu valor quando a razão entre evapotranspiração real e evapotranspiração da cultura for maior que 0,8. Os níveis de 40% de redução de produtividade apresentam 10,5% de probabilidade de ocorrência. Palavras-chave: estiagem, balanço hídrico, modelo de simulação, épocas de semeadura, perda de rendimento.